Introduction to multimedia systems - Bhatnagar, Gaurav; Mehta, Shikha; Mitra, Sugata 1952- (Academic Press, 2002)
Designed to be a general introduction to the broad field of multimedia... more specifically digital interactive multimedia. The editors have included topics such as the principles of "multiple" and "media," including sound, two-dimensional and three-dimensional graphics, animation, and text. All of these elements are stitched together by the programmer, or multimedia designer, based on the conceptualization of the designer.